PENTINGNYA PELAYANAN BIMBINGAN PRANIKAH - Estherlina Maria Ayawaila (Manna Rafflesia, 2019)
Many problems in human life, one of them problems in marriage. One way to overcome the many problems that arise in marriage by pre-marital counseling. This paper aims to provide insight into the importance of premarital guidance services. With the hope of encouraging every believer, activist and pastor to give good attention to pre-marital counseling.